Prevalence of Salmonella in Apparently Healthy Chickens in Mymensingh, Bangladesh (Microbes and Health, 2013)
Salmonella spp. are the most frequently reported cause of food-borne illnesses worldwide that are closely associated with the consumption of contaminated poultry and egg products. This study was designed to isolate and identify Salmonella, and evaluate its prevalence in chickens of different lines and ages during summer and rainy seasons. Cloacal swab samples (n=200) of apparently healthy chickens were collected. Isolated Salmonella were characterized using cultural, biochemical and serological examinations. A total of 104 samples (52%) were found to be positive for Salmonella spp. The prevalence of Salmonella spp. was significantly higher (p